Factors affecting unmet medical needs of patients with diabetes: A population‐based study - Ji Young Kim; Youngran Yang (Wiley, 2023)
Abstract Aims The purpose of this study was to identify unmet medical needs and related factors in patients with diabetes. Design A cross‐sectional study. Methods Participants included 2269 diabetes patients aged >19 years by using data from the National Health and Nutrition Examination Surveys. A complex sample design multiple logistic regression analysis was performed. Results The study found that 8.7% of diabetes patients experienced unmet medical needs, and it was found to be higher for those who thought their self‐assessed health status was unhealthy and often felt stressed in their daily life. Gender and education level had a moderating effect on income level on unmet medical needs experience. Conclusion These findings have important implications for nursing practice in the management of diabetes. Nurses can develop targeted interventions that address the specific needs of patients who are at risk for unmet medical needs, particularly those from low‐income backgrounds. By considering the factors that contribute to unmet medical needs and the moderating effect of income level, nurses can improve patient outcomes and reduce the burden of diabetes.